Isolation and Characterization of a Novel Lectin from the Edible Mushroom Stropharia rugosoannulata - Weiwei Zhang; Guoting Tian; Xueran Geng; Yongchang Zhao; Tzi Bun Ng; Liyan Zhao; Hexiang Wang (Molecules, 2014)
To date, only a few steroids have been isolated from the mushroom Stropharia rugosoannulata which can be cultivated. In this paper, a novel lectin (SRL) with a molecular weight of 38 kDa, and a unique IKSGVYRIVSWQGALGPEAR N-terminal sequence was isolated from S. rugosoannulata, which represents the first protein isolated from the mushroom. The purification methods included (NH4)2SO4 precipitation, ion exchange chromatography on CM-cellulose, Q-Sepharose, and SP-Sepharose, and gel- filtration on Superdex-75. The lectin was adsorbed on all three types of ion exchangers and was purified more than 450-fold. The lectin was stable below 70 °C (with half of the activity preserved at 80 °C), and in the presence of NaOH and HCl solutions up to a concentration of 12.5 mM and 25 mM, respectively. The hemagglutinating activity of SRL was inhibited by inulin. Cd2+ and Hg2+ ions strongly reduced the hemagglutinating activity at concentrations from 1.25 mM to 10 mM. SRL exhibited anti-proliferative activity toward both hepatoma Hep G2 cells and leukemia L1210 cells, with an IC50 of 7 μM and 19 μM, respectively. The activity of HIV-1 reverse transcriptase could also be inhibited by SRL, with an IC50 of 10 μM.